2011
DOI: 10.1097/won.0b013e318220b6bc
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Morphological Characteristics and Etiology of Pressure Ulcers in Intensive Care Unit Patients

Abstract: PU can be categorized into 4 morphological types, including a new category of leaf-shaped PU. We found that frequently repeated position changes such as lateral tilt and repeated head elevation caused deformation of the sacral skin that may play a role in PU development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The incidence of pressure ulcerations ranges from 7% to 53% in ICU patients, and aggressive approaches for prevention, including frequent change of patient position, have been proposed . However, Nanjo and et al demonstrated that frequent patient position change could instead induce pressure ulcerations by causing sacral skin deformations. Nevertheless, a recent study by the Proseva trial group found that a prolonged stay (> 16 h) in one position, the prone position, was associated with higher incidence of pressure ulcerations …”
Section: Discussionmentioning
confidence: 99%
“…The incidence of pressure ulcerations ranges from 7% to 53% in ICU patients, and aggressive approaches for prevention, including frequent change of patient position, have been proposed . However, Nanjo and et al demonstrated that frequent patient position change could instead induce pressure ulcerations by causing sacral skin deformations. Nevertheless, a recent study by the Proseva trial group found that a prolonged stay (> 16 h) in one position, the prone position, was associated with higher incidence of pressure ulcerations …”
Section: Discussionmentioning
confidence: 99%
“…Patients with PIs had different morphology and morphometry characteristics demonstrating anatomical variation. Tissue thickness findings appear to describe the presence or lack of adipose tissue distribution required as a protective mechanism over load-bearing areas 20–22 . In an attempt to determine the rationale for this finding, the researchers reviewed cases and noted that 9 of the 15 patients with PIs had BMIs from 25 to 30 kg/m 2 (overweight) or greater than 30 kg/m 2 (obesity and class 3 obesity according to the CDC) 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Tissue thickness findings appear to describe the presence or lack of adipose tissue distribution required as a protective mechanism over load-bearing areas. [20][21][22] In an attempt to determine the rationale for this finding, the researchers reviewed cases and noted that 9 of the 15 patients with PIs had BMIs from 25 to 30 kg/m 2 (overweight) or greater than 30 kg/m 2 (obesity and class 3 obesity according to the CDC). 56 On the contrary, three patients with full-thickness PIs and thinner tissue between C1 and C2 had a BMI of less than 18.5 kg/m 2 (underweight, cachexia).…”
Section: Aimmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that high pressure of more than 100 mm Hg lasting more than 8.1 hours resulted in pressure ulcers compared with blanchable redness and no redness at about 4.6 hours duration, suggesting that the system might lead to reduced frequency in turning of patients. Nanjo et al 17 suggested that frequent repositioning involving lateral tilt and head elevation might cause, instead of prevent, sacral skin "leaf-type" pressure ulcers in ICU patients. Sprigle and Sonenblum 6 suggested that published interface pressure mapping values may not be translatable to other patients elsewhere.…”
Section: Discussionmentioning
confidence: 99%